POLITIK REPRESENTASI RUMAH ASPIRASI : STUDI TENTANG RUMAH ASPIRASI BUDIMAN DI KABUPATEN BANYUMAS-CILACAP - Luavikar Alfan Cahasta (Journal of Governance, 2017)
This study is about one innovations democratic actors in efforts to democratize democracy through the installation of an institution called Aspirations House. This study will specifically address the Aspirations House that initiated by one of the members of the House of Representatives 2009-2014 period, regarding the subject and context of representation RAB. RAB has two subjects who represented, the constituency Budiman Sudjatmiko in CilacapBanyumas electoral district and Budiman it self. Using the model representation Mansbrige (2003), RAB can be identified as Promissory representation. RAB representation practice work in the context of the embodiment of a political campaign promises of Budiman Sudjatmiko during legislative elections. RAB as an alternative representation organization, run advocacy issues that concern the biggest population of constituent